2006
DOI: 10.3892/ijo.28.2.463
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel SEREX antigen, SLC2A1/GLUT1, in esophageal squamous cell carcinoma

Abstract: We have carried out SEREX (serological identification of antigens by recombinant cDNA expression cloning), and identified SLC2A1 (solute carrier family 2/facilitated glucose transporter, member 1) as an antigen recognized by serum IgG antibodies in patients with esophageal squamous cell carcinoma (SCC). The levels of serum anti-SLC2A1 antibodies (s-SLC2A1-Abs), examined by enzyme-linked immunosorbent assay using bacterially expressed glutathione-S-transferase-SLC2A1 fusion protein, were significantly higher in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 23 publications
0
41
0
Order By: Relevance
“…SEREX antigens are thought to be good candidates for the development of tumor specific vaccination therapies. We have previously reported 21 SEREX antigens of esophageal SCC (9)(10)(11)(12)(13). In the present study, we identified myomegalin as a new SEREX antigen of great interest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SEREX antigens are thought to be good candidates for the development of tumor specific vaccination therapies. We have previously reported 21 SEREX antigens of esophageal SCC (9)(10)(11)(12)(13). In the present study, we identified myomegalin as a new SEREX antigen of great interest.…”
Section: Discussionmentioning
confidence: 99%
“…In order to identify new tumor-associated antigens that may generate new serum markers for esophageal SCC, we used the method of serological identification of antigens by recombinant cDNA expression cloning (SEREX) which involves the immunoscreening of cDNA libraries prepared from tumor specimens using autologous or allogeneic sera (7). Chen et al (8) and our group (9)(10)(11)(12)(13) have succeeded in the identification of several tumor antigens for esophageal SCC. The identification of human tumor antigens recognized by the autologous host is yielding an array of target molecules for the diagnosis, monitoring, and immunotherapy of human cancer (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…E. coli JM109 cells, which contained cDNA clones recombined in pBluescript II, were cultured with or without 1 mM IPTG for 2.5 h. Cells were then washed with phosphate-buffered saline (PBS) and lysed by incubation at 100°C for 3 min in SDS sample buffer. E. coli lysate was then subjected to SDS-PAGE followed by Western blotting using 54 patient sera or 46 healthy control sera, as described [8][9][10][11].…”
Section: Western Blottingmentioning
confidence: 99%
“…High titers of serum p53 antibodies were reported to indicate a poor prognosis [6,7]. In a previous series of SEREX screenings in esophageal SCC, we identified several new tumor antigens, including TROP2, TRIM21, GLUT-1 and myomegalin [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…We also identified the following autoantibody-recognized antigens by recombinant cDNA expression cloning (SEREX) method or protein array method: TACSTD2 [12], TRIM21 [13], SLC2A1 [14], MKRN1 [15], ECSA [16], and CCNL2 [17] in esophageal squamous cell carcinoma; FIR/PUF60 in colon carcinoma [18]; SH3GL1 [19] and filamin C [20] in low-grade glioma; TLN1 in multiple sclerosis [21]; RPA2 [22] and SOSTDC1 [23] in ischemic stroke; NRD1 in acute coronary syndrome [24]; TUBB2C [25], GADD34 [26], and adiponectin [27] in DM; COPE in obstructive sleep apnea [28]; and ATP2B4 [29], BMP-1 [22,29], DHPS [30], and SH3BP5 [31] in arteriosclerosis-related diseases.…”
Section: Introductionmentioning
confidence: 99%